2005
DOI: 10.2307/20062059
|View full text |Cite
|
Sign up to set email alerts
|

Author Order and Research Quality

Abstract: We observe a great deal of heterogeneity in the manner in which author orderings are assigned both across and within academic markets. To better understand this phenomenon, we develop and analyze a stochastic model of author orderings. In our model, authors work equally hard to obtain priority in listings but linal contributions arc stochastic. Further, research outlets differ in their quality hurdles. In this setting, our simulation results are consistent with two empirical regularities. First, we lind that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 2 publications
3
23
1
1
Order By: Relevance
“…Several studies have documented this trend in economics (Engers, Gans, Grant, & King, 1999;Joseph, Laband, & Patil, 2005), in finance (Brown, Chan, & Chen, 2004), and in marketing (Brown, Chan, & Lai, 2006). An increased alphabetical ordering of coauthor names is also evident.…”
Section: Abstract International Business Research Citations Coauthmentioning
confidence: 91%
“…Several studies have documented this trend in economics (Engers, Gans, Grant, & King, 1999;Joseph, Laband, & Patil, 2005), in finance (Brown, Chan, & Chen, 2004), and in marketing (Brown, Chan, & Lai, 2006). An increased alphabetical ordering of coauthor names is also evident.…”
Section: Abstract International Business Research Citations Coauthmentioning
confidence: 91%
“…In particular, the ratio of alphabetized to non-alphabetized author lists began shrinking rapidly in 1996 from approximately 1:1 to 1:2 within the span of ten years. This pattern is not common to all research areas; in fact, alphabetization rates in ''top tier'' economics journals increased between 1978 and 2000 [12]. Thus, any explanation for this type of trend must be discipline specific and possibly even sub-discipline specific.…”
Section: Past and Present Practicesmentioning
confidence: 98%
“…In the 1990s it was suggested that it was important that the order of authors reflected their contribution to an article (Savitz, 1999). Nevertheless, although it is often perceived that the first named author has made the largest contribution to an article (van Praag & van Praag, 2008) the assignment of credit varies from discipline to discipline (Engers, Gans, Grant & King, 1999) and even within disciplines (Laband, 2002;Joseph, Laband & Patil, 2005). This impacts on some citation counting methods used in research evaluation.…”
Section: Related Literature and Research Questionsmentioning
confidence: 99%